Impeding and facilitating factors for the implementation of alcohol interventions in hospitals: a qualitative and exploratory study among Dutch healthcare professionals - Nathalie Kools; Ien van de Goor; Rob H. L. M. Bovens; Dike van de Mheen; Andrea D. Rozema (BMC, 2022)
Abstract Background Non-moderated alcohol use is more prevalent among hospitalized patients compared to the general population. However, many hospitals fail to find and intervene with people with alcohol problems. We aimed to conduct an exploration of impeding and facilitating factors experienced by healthcare professionals in implementation of alcohol interventions in Dutch general hospitals. In addition, we explored the alcohol interventions used in the selected hospitals and involved stakeholders. Methods Through a qualitative study, semi-structured telephone interviews were conducted with twenty healthcare professionals working in or in collaboration with six different general hospitals. Results Healthcare professionals indicated impeding and facilitating factors in the areas of motivation, knowledge and skills, patient characteristics, protocol, internal and external collaboration/support, resources, role suitability and societal support. Five different categories of approaches to identify and intervene with non-moderated alcohol use and 18 involved stakeholders from both inside and outside the hospital were found. Conclusions Implementation of alcohol interventions for patients in Dutch general hospitals still seems to be in its infancy. Respondents emphasized the importance of one clear protocol on how to tackle alcohol problems within their hospital, repeated training on alcohol-related knowledge and skills, (clinical) "champions" that support healthcare professionals and developing and maintaining collaborations with stakeholders within and outside the hospital.